Perdagangan Ternak dan Daging Sapi: Rekonsiliasi Kebijakan Impor dan Revitalisasi Pemasaran Domestik - I Wayan Rusastra (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2014)
EnglishFor the last decade, average national consumption of beef increases by 4.5 percent/year, with a high trend of import i.e. 21.6 percent/year compared to that of domestic beef production rate of 2.6 percent/year. Development of beef cattle need long-term investment, therefore disincentive of import policy will give substantial impact, psychologically and economically, to the farmers. The objective of this paper is to formulate the harmonization of import policy and domestic marketing in order to support the development and sustainability of beef cattle agribusiness. In the context of the Food Law No.18/2012, the import policy of feeder cattle and beef cattle is the last resort policy and should be conducted with the principle of cautiously. Coordination and consolidation between the logistic institution (Bulog) and the importer association is needed in relation to implementation of price stabilization policy effectively and efficiently. The implementation of import policy based on price reference have to be conducted in conjunction with the powerful logistic system development. The respective policy should be complemented with the enhancement of domestic marketing efficiency for the benefits of increasing beef cattle population, beef production, and the welfare of the farmers. Policy direction of livestock and beef cattle domestic marketing is to maintain meat consumption diversification, deregulation of retribution and marketing system, enhancement of the institutional and bargaining position of the farmers, as well as gradual reducing of beef cattle inter-regional trade quota complemented with production development policy of beef cattle farming. IndonesianDalam satu dasa warsa terakhir ini, rataan konsumsi nasional daging sapi meningkat dengan laju 4,5 persen/tahun, tetapi dengan laju impor yang tinggi yaitu 21,6 persen/tahun vs laju peningkatan produksi domestik hanya 2,6 persen/tahun. Pengembangan sapi potong membutuhkan investasi jangka panjang, sehingga disinsentif kebijakan impor akan memiliki konsekuensi psikologis dan ekonomi yang besar bagi peternak. Tujuan tulisan ini adalah merumuskan harmonisasi kebijakan impor dan pemasaran domestik untuk mendukung pengembangan dan keberlanjutan agribisnis sapi potong. Dalam konteks UU Pangan No.18 Tahun 2012 kebijakan impor ternak dan daging sapi adalah pilihan terakhir dan harus dilakukan dengan prinsip penuh kehati-hatian. Dibutuhkan koordinasi dan konsolidasi antar institusi parastatal (Bulog) dan asosiasi importir dalam eksekusi kebijakan stabilisasi harga secara efektif dan efisien. Kebijakan impor berbasis harga referensi harus dalam satu paket kebijakan dengan kebijakan pengembangan sistem logistik yang handal dan perbaikan efisiensi pemasaran domestik, sehingga memberikan insentif yang memadai bagi peningkatan populasi, produksi, dan kesejahteraan peternak. Arah kebijakan pemasaran ternak dan daging sapi domestik adalah menjaga diversifikasi konsumsi daging, deregulasi sistem retribusi dan tataniaga, penguatan kelembagaan dan posisi tawar peternak, dan pelaksanaan penghapusan kuota perdagangan sapi antar pulau secara terpadu dengan penguatan kebijakan pengembangan produksi usaha ternak sapi potong.